Wage dispersion and pension funds: Financialisation of non-financial corporations in the USA - Dögüs, Ilhan (PSL Quarterly Review, 2018)
The paper argues that wage dispersion between white-collar and blue-collar workers has caused the rise and expansion of pension funds in a direct and long-run structural manner in the USA. Using data from the Saez-Zucman and the St. Louis Fed’s FRED datasets, the argument is empirically analysed on yearly data for the period 1964-2012 in the USA. The results confirm the existence of a long-run relationship of causality from wage dispersion to the share of pension funds within US households’ financial wealth. Applying a vector error correction model to the data it emerges that the variance in pension funds due to wage dispersion starts to rise after the fifth period, and reaches 69% in the tenth period. .